Space-Surface Bistatic Sar Using BeiDou-2 as Illuminator - Weiming Tian; Tian Zhang; Cheng Hu; Xiaopeng Yang; Tao Zeng (2014 IEEE International Conference on Computer and Information Technology, 2014)
Space-surface bistatic synthetic aperture radar (SS-BiSAR) for local area monitoring is presented based on BeiDou-2/Compass-2 as illuminator. The time and frequency synchronization and imaging processing are mainly investigated in this paper. In the proposed method, the BiSAR signal model containing time and frequency synchronization errors is firstly set up. In the following, a time and frequency synchronization method is proposed to deal with the absence of posterior ephemeris which is a special issue of BeiDou-2 system. Then, a corresponding back-projection algorithm is deduced to deal with curved trajectory of satellite in long synthetic time. In the time and frequency synchronization method, direct signal from the satellite is used to estimate time delay and phase history and extract navigation message to acquire time and ephemeris information. The synchronization errors are estimated based on the time delay, phase history and the calculated slant range history. In the imaging processing, the signals along sum of bistatic slant ranges are phase compensated and accumulated to form the final focused image. SS-BiSAR experiments using Beidou-2 as illuminators are carried out to validate the proposed methods. The feasibility of SS-BiSAR using BeiDou-2 as transmitter is demonstrated by the imaging results of both a transponder and natural scene.